The Impact of Human Resource Aspects in Supporting Readiness for Change - Widyastuti, Fransiska; Ardiyanti, Niken (Universitas Brawijaya, Indonesia, 2024)
In this modern era, all organizations experience challenges due to environmental uncertainty. Readiness to change is an important thing that must be considered by companies when implementing change management. The aspects of human resources that affect readiness to change are employee engagement, organizational justice, and perceived organizational support. This study aimed to identify and analyze the impact of employee involvement and resistance to change on readiness to change, with organizational support as a mediating variable in change management. This research uses the SEM (Structural Equation Modeling) method with the entire population of PT PLN E. The sampling technique used is purposive sampling, with a total sample size of 250 employees. The results show that employee engagement has a positive and significant effect on perceived organizational support and readiness for change, with or without making the variable perceived organizational support a mediator. In addition, the Organizational Justice variable also has a positive and significant effect on perceived organizational support and readiness for change, with or without making perceived organizational support a mediating variable. Then the last variable, perceived organizational support, has a positive and significant effect on the readiness for change variable. If the company is able to create job satisfaction, provide skill development, establish effective communication, strengthen a positive outlook, and build confidence in success, Then success in increasing employee readiness will contribute to the successful implementation of change and achieve better organizational goals.